Entwicklung und Lage ausgewählter Fischbestände - Einschätzung des Internationalen Rates für Meeresforschung Ende 2000 - Hammer, Cornelius (2001)
During the autumn session of the ICES Advisory Committee for Fisheries Management (ACFM) the stock of the Arctic, Northern and Southern Shelf, North Sea and Skagerrak have been analysed and assessed, as well as the mackerel and horse mackerel, sardine, anchovy and Pandalus, eel and harp and hooded seals. For a number of stocks ICES recommends a reduction in fishing mortality. Moreover, ICES recommends for many stocks to establish recovery and management plans, to safe guarda continuous development of the stocks towards safe biological limits. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery Research in 2010.